The ethical use of crowdsourcing. (10th October 2017) - Standing, Susan; Standing, Craig
Abstract : Crowdsourcing has attracted increasing attention as a means to enlist online participants in organisational activities. In this paper, we examine crowdsourcing from the perspective of its ethical use in the support of open innovation taking a broader system view of its use. Crowdsourcing has the potential to improve access to knowledge, skills, and creativity in a cost‐effective manner but raises a number of ethical dilemmas. The paper discusses the ethical issues related to knowledge exchange, economics, and relational aspects of crowdsourcing. A guiding framework drawn from the ethics literature is proposed to guide the ethical use of crowdsourcing. A major problem is that crowdsourcing is viewed in a piecemeal fashion and separate from other organisational processes. The trend for organisations to be more digitally collaborative is explored in relation to the need for greater awareness of crowdsourcing implications.